Implementation of Islamic Values in Stories Prophet Ismail As. In Education - Ummi Hanifaa; Siti Ardianti; Gadis Ayuni Putri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The tales of the previous prophets teach us a lot that we can use in our daily lives as Muslims. The moral lessons in each story are unique and of high quality, encouraging readers to lead peaceful and content lives. The same can be done in education. In this composition, we make sense of how the narrative of the prophet Ismail is executed in training. The prophetic legacy and life story of Prophet Ismail As. Additionally, it has educational values like the value of akhlakul karimah, the value of democratic debate, and the value of monotheism. The values derived from the story of the Prophet Ismail As also include educational objectives and materials, educators with all of their competencies, students with their academic ethics, and effective educational methods.